The Farm Press, Reform and Rural Change, 1895-1920 - Fry, John J. (Studies in American Popular History and Culture, 2005)
This project contributes to our understanding of rural Midwesterners and farm newspapers at the turn of the century. While cultural historians have mainly focused on readers in town and cities, it examines Midwestern farmers. It also contributes to the "new rural history" by exploring the ideas of Hal Barron and others that country people selectively adapted the advice given to them by reformers. Finally, it furthers our understanding of American farm newspapers themselves and offers suggestions on how to use them as sources.